Assessment of the Bone Density of Nomadic Fulani Herdsmen in Northern Nigeria Using Calcaneal Ultrasonography - Laabes, Emmanuel P. (Medscape, 2008)
CONTEXT: Osteoporosis is characterized by decreased bone density and increased bone fragility. Genetics, diet, and physical activity are established determinants of bone density. The seminomadic Fulani of northern Nigeria trek long distances on foot daily to graze and water their animals, and have access to calcium-rich dairy products. OBJECTIVE: We sought to determine whether the high level of physical activity and presumed calcium-rich diet of the Fulani would promote a higher bone density, compared with their relatively inactive counterparts in the general population. DESIGN: Cross-sectional study. SETTING: Three Fulani settlements (Toro, Tilden Fulani, and Magaman Gumau) within 5 to 15 kilometers of Jos Metropolis on the Jos Plateau in northern Nigeria. PATIENTS: We assessed the calcaneal characteristics of a consecutive sample of 51 active seminomadic Fulani men using the Lunar Achilles+ ultrasonometer. MAIN OUTCOME MEASURES: Calcaneal broadband ultrasound attenuation (BUA), speed of sound (SOS), stiffness index (SI), and SI T-scores. RESULTS: The mean age of the herdsmen was 26 ± 9 years (range, 16 to 49), and the mean BMI was 19.9 ± 2.3 kg/m(2). The mean BUA was 124 ± 13 dB/MHz (95% CI, 120 to 128), the mean SOS was 1572 ± 33 m/s (95% CI, 1563 to 1581), the mean SI was 102 ± 17 (95% CI, 97 to 107], and the mean SI T-score was −0.74 ± 0.97 (95% CI, −0.47 to 1.01]. The mean SI was 1 T-score unit below that of an age-matched cohort in the general population. CONCLUSION: Fulani herdsmen have a theoretically increased risk for bone fracture in a background of low BMI and potentially high calcium intake.